How benchmarking can support the selection, planning and delivery of nuclear decommissioning projects. (August 2017) - Invernizzi, Diletta Colette; Locatelli, Giorgio; Brookes, Naomi J.
Abstract: Nuclear Decommissioning Projects and Programmes (NDPs) are jeopardized by several risks, long schedule and cost estimates that lay in the range of hundreds of billions of pounds. Moreover, in some countries, these estimates keep increasing and key stakeholders have a limited understanding of the determinants that engender this phenomena. Benchmarking refers to the process of comparing projects in order to identify best practices and generate ideas for improvement. However, even if it is the envisaged approach to tackle the decommissioning challenges (and due to the NDPs' uniqueness), until now, benchmarking has been only partially used. This paper proposes an innovative methodology to benchmark decommissioning projects, both from the nuclear and non-nuclear industry, within the UK and worldwide. From this cross-sectorial and cross-country analysis, it is possible to gather a list of key NDPs' characteristic and statistically test their correlation with the project performance. The ultimate aim of the research underpinning this paper is to investigate the possible causation between the NDPs' characteristics and the NDPs' performance and to develop guidelines to improve the selection, planning and delivery of future NDPs. Highlights: Nuclear Decommissioning is affected by several risks and uncertainties. Decommissioning schedule and cost estimates are hard to predict and rarely reliable. Benchmarking is the envisaged approach to tackle the decommissioning challenges. This paper presents an innovative methodology to benchmark NDPs. Performance measurement is key to implement this methodology.